On the Lunar Origin of Near-Earth Asteroid 2024 PT5 - Theodore Kareta; Oscar Fuentes-Muñoz; Nicholas Moskovitz; Davide Farnocchia; Benjamin N. L. Sharkey (The Astrophysical Journal Letters)
The near-Earth asteroid (NEA) 2024 PT5 is on an Earth-like orbit that remained in Earth's immediate vicinity for several months at the end of 2024. PT5's orbit is challenging to populate with asteroids originating from the main belt and is more commonly associated with rocket bodies mistakenly identified as natural objects or with debris ejected from impacts on the Moon. We obtained visible and near-infrared reflectance spectra of PT5 with the Lowell Discovery Telescope and NASA Infrared Telescope Facility on 2024 August 16. The combined reflectance spectrum matches lunar samples but does not match any known asteroid types—it is pyroxene-rich, while asteroids of comparable spectral redness are olivine-rich. Moreover, the amount of solar radiation pressure observed on the PT5 trajectory is orders of magnitude lower than what would be expected for an artificial object. We therefore conclude that 2024 PT5 is ejecta from an impact on the Moon, thus making PT5 the second NEA suggested to be sourced from the surface of the Moon. While one object might be an outlier, two suggest that there is an underlying population to be characterized. Long-term predictions of the position of 2024 PT5 are challenging due to the slow Earth encounters characteristic of objects in these orbits. A population of near-Earth objects that are sourced by the Moon would be important to characterize for understanding how impacts work on our nearest neighbor and for identifying the source regions of asteroids and meteorites from this understudied population of objects on very Earth-like orbits.